Influence of composite type and light irradiance on color stability after immersion in different beverages. Issue 5 (19th June 2018) - Alberton Da Silva, Victória; Alberton Da Silva, Simone; Pecho, Oscar E.; Bacchi, Atais
Abstract: Objective: The aim of this study was to evaluate the color stability of two resin‐based composites photo‐activated by two light curing units (LCU) with different irradiances. Materials and Methods: Hundred disc‐shaped specimens (2‐mm thick) of a nanofilled (FZ‐ Filtek TM Z350 XT, 3M ESPE) and a microhybrid (ED—Empress ® Direct, Ivoclar Vivadent) composites were photo‐activated with two LCU: Valo ® Cordless, Ultradent (VA—1800 mW/cm 2 ) or Radii‐cal, SDI (RA—900 mW/cm 2 ). Samples (n = 5) were immersed during 12 days in distilled water (WT), orange juice (OJ), red wine (RW), coffee (CF), or Brazilian tea (BT). CIELAB coordinates were obtained using a spectrophotometer (Easyshade 4.0, Vita Zahnfabrik) before ( T 0 ) and after ( T 1 ) immersion. CIEDE2000 color difference (Δ E 00 ) and whiteness index for dentistry (WID ) were calculated. Data was analyzed by two‐way ANOVA and Tukey's test (α = 0.05%). Results: FZ light‐activated by VA showed higher L * and WID values ( T 0 ) and lower Δ E 00 values after immersion in WT, OJ, and RW. However, there was no effect of both factors on Δ E 00 when samples were immersed in BT and CF. ED light‐activated by RA showed significant higher C * values ( p ≤ .05). Conclusions: The nanofilled composite photo‐activated with higher irradiance showed greater L * and WID values and better color stability. However, all samples immersed in colored beverages showed ΔE00 values above the acceptability threshold. Clinical Significance: Initial color of resin‐based composites can change after immersion in staining beverages. However, the best color stability was obtained by the nanocomposite photo‐activated by a light‐curing unit of higher irradiance.